Natural and Anthropocene fluxes of trace elements in estuarine sediments of Galician Rias. (5th November 2017) - Álvarez-Vázquez, Miguel Ángel; Caetano, Miguel; Álvarez-Iglesias, Paula; Pedrosa-García, María del Canto; Calvo, Susana; De Uña-Álvarez, Elena; Quintana, Begoña; Vale, Carlos; Prego, Ricardo
Abstract: The Anthropocene has been proposed as a new geo-stratigraphic epoch where humans have become a global factor affecting the ecosystems. Estuarine sediments constitute a biogeochemical reservoir where trace elements (TEs) from natural sources mix with a fraction generated by human activities. This study assessed the natural lithogenic imprint of TEs from uncontaminated sedimentary records to study anthropogenic changes. Sediment cores were sampled in the estuarine part of the low populated and low industrialized rias of Ares (A), Betanzos (B) and Cedeira (C), which are located in the NW of the Iberian Peninsula. Cores were dated by the 210 Pb method, covering up to the last century period. Sedimentation rates (in mm yr −1 ) were 3.4 ± 0.6 (older than 1961) and 8.2 ± 3.2 (younger than 1961) for core A, 0.9 ± 0.2 (<1940) and 4.2 ± 2.3 for core B, and 13.4 ± 1.4 for core C. The background fluxes of TEs were in the ranges of (in g m −2  yr −1 ) 50–560 for Al and Fe, 20–320 for POC and 8–100 for PS, and (in mg m −2  yr −1 ) 20–120 for As, 0.2–2.0 for Cd, 7–110 for Co, 40–870 for Cr, 20–230 for Cu, 0.1–0.6 for Hg, 290–2800 for Mn, 4–24 for Mo, 20–410 for Ni, 20–150 for Pb, 60–800 for V and 70–700 for Zn. The three cores showed an anthropogenic influence since the mid-20th century. The detected human impact during the Anthropocene was due to the Eume River damming and As-Pontes lignite mining (the largest mine open-pit in the Iberian Peninsula) in core A, by bridge/road constructions, vehicles emissions and river mouth urbanization in core B, and changes in land use in core C. Sediment accumulation rates increased 2.4 (core A) and 4.7 times (core B) while TEs fluxes increased 2.4 times in core A and between 3.6 and 5.1 times in core B. Pre-industrial sedimentary records showed the lithogenic differences of the drainage basins, mainly granitic watersheds for cores A and B and the prevalence of basic rocks of the Ortegal Geological Complex for core C. This explains the high concentrations and fluxes of Cr, Ni and V of core C. The different lithogenic imprints highlight the value of using local background references in contamination studies, such as those on the Anthropocene influence in estuaries, which occurred after the Spanish Civil War in the studied rias. Highlights: Estuarine sediment cores in three Galician Rias were dated and background levels and TEs fluxes established by the first time. During the Anthropocene the TEs fluxes to the sediment increased between 2.4 and 5.1 times in two of three studied estuaries. Lithology, dam, mining, vehicles' emissions and river mouth urbanization are the main reasons of TEs inputs to ria sediments. Studied cores show that the Anthropocene influence took place after the Spanish Civil War, at the mid-20th century.